Improving Flexibility in Manufacturing Using a Family Ordering System for Long Lead Time Component - Ooi, Chee Keong (2005)
Most manufacturers face challenges from inaccurate forecast, regular plan changes, back log and capacity problems. As a result, their purchasers rely heavily on the material suppliers to provide greater flexibility in the event of production schedule changes. Oftentimes, manufacturers attempt to push material forecast risks to the material suppliers. In order to overcome the risks taken to achieve flexible manufacturing or supply chain management, this study will address the issues and methods to accommodate production schedule changes in a short time-frame.